HUBUNGAN POLA ASUH DENGAN STATUS GIZI ANAK BALITA DI DESA BONGOMEME KECAMATAN DUNGALIO KABUPATEN GORONTALO - Sofyawati Talibo; Sri Yolanda Tuna (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2016)
ABSTRACT Nutritional problems are influenced by many factors that influence each other in a complex manner. At the household level, the state of nutrition is influenced by the ability of households to provide sufficient quantities and types of food and parenting styles that are influenced by educational, behavioral and household health factors. One of the causes of malnutrition in children under five is due to inadequate parenting (Tomayahu 2011 in Soekirman 2000).This study aims to determine the relationship between parenting and nutritional status of children under five in Bongomeme Village, Dungaliyo District, Gorontalo Regency.This study includes the type of analytic research. Populassi as many as 109 people, the sample is 86 people. Free variables are parenting and the dependent variable is the nutritional status of children under five. Data analysis in this study used the